Analisis Manajemen Layanan Teknologi Informasi dalam Proses Pemesanan Produk melalui Aplikasi Klik Indomaret pada PT Indomarco Prismatama - Fenny Purwani; Nabila Miftha Huljanah; Kristin Kristin; Apriani Apriani; Dini Hermiyani (Jurnal Riset Sistem Informasi, 2025)
This study aims to analyze information technology service management (IT Service Management) in the product ordering process through the Klik Indomaret application developed by PT Indomarco Prismatama. As consumer demand for fast and efficient online shopping services increases, the company is required to provide a reliable, responsive, and user-friendly IT service system. This research employs a qualitative approach, using data collection techniques such as interviews, observations, and document analysis. The analysis is based on the ITIL (Information Technology Infrastructure Library) framework to evaluate the effectiveness of service management in supporting core business processes. The findings indicate that although the Klik Indomaret application has positively contributed to streamlining the ordering process and improving customer satisfaction, several challenges remain, such as delays in stock data updates, system disruptions, and limited integration among IT services. Recommendations include enhancing system monitoring, optimizing the service desk, and strengthening incident management strategies. These findings are expected to serve as a foundation for the future development of more robust IT services.